2014
DOI: 10.1080/17470919.2014.969406
|View full text |Cite
|
Sign up to set email alerts
|

Emotional processing in Colombian ex-combatants and its relationship with empathy and executive functions

Abstract: In this work, the neural correlates of emotional processing in Colombian ex-combatants with different empathy profiles were compared to normal controls matched for age, gender and educational level. Forty ex-combatants and 20 non ex-combatants were recruited for this study. Empathy levels as well as executive functions were measured. Empathy level was used to create three groups. Group 1 (G1) included ex-combatants with normal empathy scores, and Group 2 included ex-combatants with low scores on at least one e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 75 publications
(84 reference statements)
2
27
0
2
Order By: Relevance
“…Further meta‐analysis of ERP investigations found that the activity of P3 and late positive potential components could reveal participants’ empathy, whereas the early N1 and N2 components were not reliable in predicting empathy (Coll, ). P3 and late positive potential components also proved to be closely related to EF (Tobon et al, ; White & Grant, ). On the other hand, Van Overwalle () conducted a meta‐analysis to explore the location and function of brain areas involved in social cognition and found that inferring the temporary and enduring states of others and the self, as well as interpersonal norms, engages the medial prefrontal cortex, an area closely associated with EF.…”
Section: Discussionmentioning
confidence: 99%
“…Further meta‐analysis of ERP investigations found that the activity of P3 and late positive potential components could reveal participants’ empathy, whereas the early N1 and N2 components were not reliable in predicting empathy (Coll, ). P3 and late positive potential components also proved to be closely related to EF (Tobon et al, ; White & Grant, ). On the other hand, Van Overwalle () conducted a meta‐analysis to explore the location and function of brain areas involved in social cognition and found that inferring the temporary and enduring states of others and the self, as well as interpersonal norms, engages the medial prefrontal cortex, an area closely associated with EF.…”
Section: Discussionmentioning
confidence: 99%
“…Ex-combatants have shown atypical EP expressions (Boxer et al, 2011; Tobon et al, 2015; Quintero-Zea et al, 2017). They present with an increased reactivity to emotional images (i.e., International Affective Picture System—IAPS) revealed via late electrophysiological responses that are associated to a reduction in their empathic disposition (Tobon et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…They present with an increased reactivity to emotional images (i.e., International Affective Picture System—IAPS) revealed via late electrophysiological responses that are associated to a reduction in their empathic disposition (Tobon et al, 2015). A more recent study has confirmed that modulations of Event Related Potentials elicited during the EP of faces or words together with the analysis of aggressive responses and social interactions can distinguish between ex-combatants and controls (Quintero-Zea et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important population to investigate this hypothesis is that of ex-combatants. They represent a non-clinical group with well-documented impairments in EP (Tobón et al, 2015; Quintero-Zea et al, 2017; Trujillo et al, 2017). Ex-combatants typically display diminished empathic expressions (McCarroll et al, 2010; Slep et al, 2010), increased levels of aggression and violence (Jakupcak et al, 2007; Taft et al, 2007; Gallaway et al, 2012), high proportion of a wide variety of mental disorders (Taft et al, 2007; Weierstall et al, 2013; Kaplan and Nussio, 2015, 2016) as well as high emotional reactivity reflected via emotion related ERP components (IAPS; Lang et al, 1988; Tobón et al, 2015).…”
Section: Introductionmentioning
confidence: 99%